Pembiasaan Membaca Surat Al-Kahf pada Malam atau Hari Jum’at di komunitas ODOJ DPA SUMEDANG: English - Nugraha, Rizki Sabar (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
This study discusses reading Surah Al-Kahf on Friday nights or Fridays routinely as part of the One Day One Juz (ODOJ) community in Dewan Pengurus Area (DPA) Sumedang. This routinely specifically as application of the Living Quran concept in which the Quran is alive, both by its dynamic and active recitations and application of the words and commands of the Quran in daily life. This research used a qualitative and descriptive methodology by directly observing and questioning to the leaders and members of the ODOJ in DPA Sumedang. The findings reveal that often reading Surah Al-Kahf on Friday nights or Fridays makes their spiritual sense high, and prove their support for each other by implementing various community activities. It is because by the Sa’id al-Khudri hadith narration that those who often read Surah Al-Kahf on Friday nights or Fridays will be given a light between the two Friday nights. Meanwhile, this routine also will improve the social cohesion and make the community more serious in learning to practice Islamic teachings.